Transaction Cost Analysis on Revenues and Profits of Red Chili Farming - Saidah, Zumi; Harianto, Harianto; Hartoyo, Sri; Asmarantaka, Ratna Winandi (School of Business, Bogor Agricultural University (SB-IPB), 2019)
This research aimed to analyze the transaction cost structure and the effect of transaction costs on the revenue and profit of red chili farming. The analytical methods used were Transaction Cost Economic (TCE) analysis and multiple regression analysis. This research was conducted in Garut Regency, West Java, on 145 farm households. The research results showed that the highest percentage of transaction cost components was at implementation costs of 25.1 percent, followed by information search costs of 23.1 percent and negotiation costs of 22.3 percent. The number of transaction costs formed in red chili farming was IDR 3,990 727.74 per year. The ratio of transaction costs to total costs was 0.0285. This indicated that farmers had to issue 2.85 percent of the total costs for transaction costs. In addition, the percentages of transaction costs for revenue and profit of red chili farming were 4.65 and 5.27 percent respectively. The results also showed that five variables had significant effects on the benefits of red chili farming. The five variables included the price of chili seeds, manure, insecticides, labor wages, and transaction costs.